2009
DOI: 10.1111/j.1365-246x.2009.04315.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental magnetic responses of urbanization processes: evidence from lake sediments in East Lake, Wuhan, China

Abstract: S U M M A R YWe present a study on the environmental magnetic response to urbanization processes from nine sediment cores from East Lake in Wuhan, China. The concentration of magnetic particles, heavy metals and organic matter in the upper 2-18 cm of the sediment cores have been significantly elevated due to the input of coarse magnetite grains from industrial (e.g. power generation and steelmaking) and other anthropogenic activities (e.g. vehicle emissions). Concentration-related magnetic parameters, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 49 publications
1
22
0
1
Order By: Relevance
“…In addition to the commercial activities mentioned early, further industrial plants, such as foundries and cement plants exist (Yang, Liu, Zeng, & Chan, 2009). More importantly, the Lake plays a substantial role in industrial and agricultural production, daily life, aquaculture, and tourism.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the commercial activities mentioned early, further industrial plants, such as foundries and cement plants exist (Yang, Liu, Zeng, & Chan, 2009). More importantly, the Lake plays a substantial role in industrial and agricultural production, daily life, aquaculture, and tourism.…”
Section: Study Areamentioning
confidence: 99%
“…Moreover, the scale of built-up construction surrounding the East Lake is still expanding and the population is becoming denser . Therefore, the East Lake picturesque area faces severe ecological problems such as lake eutrophication affected by the large domestic sewage, oil waste from catering industry and the discharge of industrial and agricultural waste (Huang, Liu, Fang, & Zhao, 2013;Wilson et al, 2008;Yang et al, 2009), coal gasification (tar) and coking plants, and many more have been piled up in the Qingshan industrial vicinity.…”
Section: Study Areamentioning
confidence: 99%
“…Historically, the BELWN was an open lake system connected to the Yangtze river before 1957. Due to the rapid urban development, the BELWN became a disconnected lake system and was isolated from the Yangtze river (Du, 1998;Yang et al, 2009;Huang et al, 2013). In 1950, the BELWN had abundant aquatic plants and clear water (Chen et al, 1975;Wu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Their deposition thus may be associated with the enhancement of both magnetization and concentration of pollutants in environmental matters (e.g., topsoils, sediments, fly ashes, and road dusts, etc. ; Petrovský and Ellwood 1999;Ng et al 2003;Lu and Bai 2006;Magiera and Zawadzki 2007;Hanesch et al 2007; Sharma and Tripathi 2008;Lu et al 2009;Liu et al 2009;Yang et al 2007aYang et al , 2009Bućkol et al 2010). Xie et al (1999)'s study on the street dusts from Liverpool, UK, suggested that organic matter contents significantly correlate with some magnetic concentration-related parameters, and that the main magnetic carriers are a multi-domain (MD) ferrimagnetic phase with a small contribution of single-domain (SD) and antiferromagnetic grains.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic studies of roadside dust from Seoul, Korea, throughout a 13-month period, demonstrated that seasonal mapping using a mean apparent magnetic concentration (ACM) could be highly informative on the investigation of spatio-temporal pollution characteristics in urban areas (Kim et al 2009). These works have demonstrated that magnetic methods can be employed not only for identification of sources of contaminants, but also as a complementary tool for the routinely employed geochemical methods, which are known to be more time consuming, tedious, and expensive (Hoffmann et al 1999;Xie et al 1999Xie et al , 2001Ng et al 2003;Spiteri et al 2005;Prajapati et al 2006;Magiera and Zawadzki 2007;Hanesch et al 2007;Sharma and Tripathi 2008;Blaha et al 2008;Lu et al 2009;Yang et al 2007aYang et al , 2009Kim et al 2007Kim et al , 2009.…”
Section: Introductionmentioning
confidence: 99%